Targeting DNA damage in SCLC. (December 2017) - Foy, Victoria; Schenk, Maximilian W.; Baker, Katie; Gomes, Fabio; Lallo, Alice; Frese, Kristopher K.; Forster, Martin; Dive, Caroline; Blackhall, Fiona
Highlights: SCLC is characterised by high proliferation and rapid development of chemo resistant disease. SCLC is reliant on functional DNA damage repair pathways and cell cycle checkpoints to flourish. Recently there has been improved understanding of strategies to exploit DNA repair mechanisms' for therapeutic benefit. Abstract: SCLC accounts for 15% of lung cancer worldwide. Characterised by early dissemination and rapid development of chemo-resistant disease, less than 5% of patients survive 5 years. Despite 3 decades of clinical trials there has been no change to the standard platinum and etoposide regimen for first line treatment developed in the 1970's. The exceptionally high number of genomic aberrations observed in SCLC combined with the characteristic rapid cellular proliferation results in accumulation of DNA damage and genomic instability. To flourish in this precarious genomic context, SCLC cells are reliant on functional DNA damage repair pathways and cell cycle checkpoints. Current cytotoxic drugs and radiotherapy treatments for SCLC have long been known to act by induction of DNA damage and the response of cancer cells to such damage determines treatment efficacy. Recent years have witnessed improved understanding of strategies to exploit DNA damage and repair mechanisms in order to increase treatment efficacy. This review will summarise the rationale to target DNA damage response in SCLC, the progress made in evaluating novel DDR inhibitors and highlight various ongoing challenges for their clinical development in this disease.